Analisis Kesesuaian dan Daya Dukung Kawasan Wisata Pantai (Studi Pantai Indah Sergang Laut di Pulau Singkep) - Attur Mudzy Domo; Zulkarnaini Zulkarnaini; Dessy Yoswaty (Universitas Riau, 2017)
This research has been conducted in March until July 2017 in the tourist area of Pantai Indah Sergang Laut of Singkep Island of Lingga Regency. This study aims to analyze the suitability of tourism and the carrying capacity of the region and formulate tourism area management strategies. The research used survey method and descriptive analysis. Primary data were collected through direct measurements and interviews using questionnaires. The research results have suitability of tourism of the Pantai Indah Sergang Laut according to the index of 91%. Ecological carrying capacity of 1.174 persons days-1 for the 2.02 hectare coastal area so that the visitor activity and the sustainability of the area can be well maintained, have a good social support and the development of this tourist attraction has a good effect on the level of tourism business revenue. From SOAR analysis, there are three alternative strategies to develop this tourism object, namely (a) optimizing the potential, capacity and public participation to realize sustainable tourism management, (b) strengthening the existing tourist attraction to enhance competitiveness in attracting tourist and segment broader markets, and (c) the development of tourism partnerships to improve the quality and improvement of tourism economics in supporting regional development. Therefore, good coordination among stakeholders related to the implementation of alternative strategies has been formulated so as to realize sustainable tourism management.